2021
DOI: 10.3390/sexes2040040
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Linkages between Substance Use, Natural Disasters, Pandemics, and Intimate Partner Violence against Women: A Rapid Review in the Context of COVID-19

Abstract: Rates of intimate partner violence (IPV) and substance use have risen during the COVID-19 pandemic, with potentially enduring effects on women’s health. A rapid review was conducted on IPV and women’s substance use in the context of the COVID-19 pandemic. The rapid review explored two separate research questions with a view to integrate the literature related to: (1) containment, social isolation, pandemics, disasters, lockdowns, and IPV; and (2) the relationships between substance use and IPV. Two different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…Factors like addiction and stress related to the floods were identified as potential contributors to such violence. These findings are consistent with other studies that have demonstrated an increase in various forms of violence during natural disasters (Brabete et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Factors like addiction and stress related to the floods were identified as potential contributors to such violence. These findings are consistent with other studies that have demonstrated an increase in various forms of violence during natural disasters (Brabete et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In the COVID-19 pandemic speci cally, the combination of stay-at-home orders and the economic impact of the crisis could exasperate factors associated with risk of VAW which, during normal circumstances, include men's unemployment, housing insecurity, low wages, childcare strains, social isolation, and other predisposing personal factors such as histories of child maltreatment against men (20,21). The economic strain apparent in the early pandemic (22) also may have adversely affected situational coping mechanisms, such as anxiety, depression, and substance abuse, which heighten the immediate risk for IPV perpetration (23)(24)(25).…”
mentioning
confidence: 99%
“…Reasons that may deter someone from seeking help for an intentional injury during the pandemic include concern about burdening the health care system, social stigma or fear of aggravating a domestic violence situation, especially when more time is being spent at home. [38][39][40] In our study, we observed that hospital discharges for substance -related injuries that involved alcohol, opioids, cannabis, hallucinogens, tobacco, volatile solvents, other psychoactive substances and polysubstance increased during the first year of the pandemic. Other Canadian surveillance work has reported an increase in discharges for harms related to alcohol (10%), opioid (30%) and cannabis (14%) during the pandemic.…”
Section: Discussionmentioning
confidence: 61%